Pengaruh Kinerja dan Kualitas Pelayanan Petugas Boarding Gate terhadap Kepuasan Penumpang Citilink di Bandara Juanda - Reznandya Calista Putri; Ristiani Ristiani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Bag inspection aims to ensure compliance with baggage regulations for flight safety. However, it was found that some officers were not meticulous and acted unfairly during the bag inspection process. The lack of responsiveness and minimal empathy from the officers will affect passenger satisfaction. This condition indicates the need for improvement in performance and service quality to maintain passenger satisfaction and the company's image. This research uses a quantitative method, with data collection techniques in the form of questionnaires. The study samples passengers using Citilink Airlines at Juanda International Airport Surabaya, totaling 100 respondents. The data analysis techniques used include instrument testing, classical assumption testing, multiple linear regression equations, hypothesis testing, and the coefficient of determination using the SPSS (Statistical Product and Service Solutions) application. The research results show that performance and service quality have a positive and significant effect on passenger satisfaction of Citilink Airlines at Juanda International Airport Surabaya. The regression coefficients for performance are 0.479 and for service quality are 0.318, with significance values of 0.000 and 0.001, respectively (<0.1), as well as an F-test of 0.000 which indicates the simultaneous effect of both. The adjusted r square value of 0.494 indicates that 49.4% of passenger satisfaction is influenced by performance and service quality, while the remaining 50.6% is influenced by factors outside of the study.